Graphene-based dual-band independently tunable infrared absorber. Issue 33 (8th August 2018) - Sun, Peng; You, Chenglong; Mahigir, Amirreza; Liu, Tongtong; Xia, Feng; Kong, Weijin; Veronis, Georgios; Dowling, Jonathan P.; Dong, Lifeng; Yun, Maojin
Abstract : Absorption peaks can independently tune each resonant frequency by only changing the Fermi energy level of one. Abstract : In this paper, we theoretically demonstrate a dual-band independently tunable absorber consisting of a stacked graphene nanodisk and graphene layer with nanohole structure, and a metal reflector spaced by insulator layers. This structure exhibits a dipole resonance mode in graphene nanodisks and a quadrupole resonance mode in the graphene layer with nanoholes, which results in the enhancement of absorption over a wide range of incident angles for both TE and TM polarizations. The peak absorption wavelength is analyzed in detail for different geometrical parameters and the Fermi energy levels of graphene. The results show that both peaks of the absorber can be tuned dynamically and simultaneously by varying the Fermi energy level of graphene nanodisks and graphene layer with nanoholes structure. In addition, one can also independently tune each resonant frequency by only changing the Fermi energy level of one graphene layer. Such a device could be used as a chemical sensor, detector or multi-band absorber.